Enfolding wholes in parts: quantum holography and International Relations. (September 2020) - Pan, Chengxin
This article stands at the intersection between the relational turn in International Relations (IR) and the quantum turn in the social sciences (and more recently in IR as well). The relational turn draws much-needed attention to the centrality of relations in global politics, yet its imprecise conceptualization of whole-part relations casts shadow over its relational ontological foundation. The quantum turn, meanwhile, challenges the observed–observer dichotomy as well as the classical views about causality, determinacy, and measurement. Yet, despite their common stance against the Newtonian ontology, the relational and quantum turns have largely neglected each other at least in the IR context. This article aims to bridge this gap by introducing a quantum holographic approach to relationality. Drawing on theoretical physicist David Bohm's work on quantum theory and his key concepts about wholeness and the implicate order, the article argues that the world is being holographically (trans)formed: its parts are not only parts of the whole, but also enfold the whole, like in a hologram. This quantum holographic ontology contributes to both a clearer differentiation between internal/implicate relations and external/explicate relations and a renewed emphasis on wholeness and whole-part duality. In doing so, it not only provides new conceptual tools to rethink IR as holographic relations which involve the dynamic processes and mechanisms of enfoldment and unfoldment, but also has important policy and ethical implications for the conduct of "foreign" relations and for transforming the way we think about identity, survival, relationship, and responsibility.